PENDEKATAN ARSITEKTUR EKOLOGIS PADA PUSAT PENGELOLAAN SAMPAH DI SURAKARTA - Triana Puji Rahayu; Sri Yuliani; Tri Joko Daryanto (ARSITEKTURA, 2017)
The design of Waste Managament Center in Surakarta with Ecological Architecture approach is based on three considerations. First, waste problems in Indonesia need more solutions than just bin the waste, but the waste needs to be disposed properly. Second, Surakarta’s landfills is already overloaded because of the increase of waste produced. Third, there is the urge to applied ecological architecture to create a harmonious atmosphere between human and environment. This Waste Management Center designed to accomodate waste processing activity and with another supportive activities as a public facility. The method to design is problem solving by  reviewing ecological theories and applied it to the architectural component (space, site, mass and facade, structure and utility). Ecological architecture approach is applied to create a holistic design that enrich the quality of the environment and the lives of those who use them. Also, it is applied to create a harmonous atmosphere that could change society’s paradigm that waste management facility is not a disgusting dirty place but it is a clean, comfortable and eco-friendly living place to visit that leads to stimulate the visitor to not just bin the waste but dispose the waste properly.